KETERAMPILAN VARIASI MEDIA DALAM PROSES BELAJAR MENGAJAR SEJARAH DI SMA PGRI 3 PADANG - Sari, Lili Nur Indah (Pendidikan Sejarah, 2014)
The background of the research is about ability of variation media which is not yet done with the real material at SMA PGRI 3 Padang. Variation media includes listener media, seeing media, audio visual media. The purpose of the research is 1) to express the ability of teacher uses variation media in teaching learning process at SMA PGRI 3 Padang. 2) to state challenge whatever the teacher is happened by using variation media in teaching learning process at SMA PGRI 3 Padang. Kinds of the research are about evaluative study with qualitative analysis where location at SMA PGRI 3 Padang. Meanwhile, informant in this research includes history teacher which is taught at class X and XII amount 2 persons. Some students and headmasters toward observation technique, interview, and documentation study using RPP. The data analysis is examined by using triangulation data and from data is collected and analyzed with interactive that are data collection, reduction data, showing data and conclusion. From the result of research show that 1) Variation media in teaching learning process is still low and almost does not use media at class. 2) Least the teachersâ understanding about function of media in lesson. 3) Least prepare the tools and things from the school and teacher which does not effort self media that is needed in teaching. Based the result of research can be concluded that 1) least the teachersâ understanding is about important of using media in teaching learning process especially history lesson. 2) There are not effort to search or make self media that is needed. 3) Least prepare something from school with media which is needed by the teacher in learning activity.